1990
DOI: 10.1007/bf00844735
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial consequences of traumatic injury

Abstract: Long-term stress experienced by trauma patients was assessed for a sample of 137 patients treated at a large urban trauma center after suffering traumatic injuries resulting from motor vehicle/motorcycle accidents, falls, pedestrian accidents, and stabbing and gunshot wounds. Levels of psychological distress reported 3 to 39 months after the accident were considerable, but a measure of injury severity commonly used in critical care settings was not a good predictor of psychosocial outcome. The subjective impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…26 This research confirms the importance of social support for facilitating recovery from injury. [27][28][29] Support from friends, family and neighbours was regarded by participants as extremely important especially during the first few weeks/months after leaving hospital. This is when many were incapacitated and simple everyday tasks were difficult, or for some impossible to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…26 This research confirms the importance of social support for facilitating recovery from injury. [27][28][29] Support from friends, family and neighbours was regarded by participants as extremely important especially during the first few weeks/months after leaving hospital. This is when many were incapacitated and simple everyday tasks were difficult, or for some impossible to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 137 people who had severe injuries resulting from road accidents, falls, pedestrian accidents, stabbings and gunshot wounds, Landsman 6 found a high level of intrusive images and memories and psychiatric symptomatology. Church and Vincent 7 found in their sample of 29 individuals who had su ered a medical accident that 50% had clinically relevant levels of intrusion and 32% avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Malt et al found that 19% of people who were accidentally injured (most in MVAs) reported a major decline in their psychological health following the accident. Similarly, it has been found that 40% of traumatically injured individuals exhibit clinically elevated scores on the Brief Symptom Inventory (Landsman et al, 1990)) exceeding normative levels of depression, anxiety, hostility, somatization, and obsessivecompulsive disorders. Children involved in MVAs have demonstrated similar symptomatology (Jaworowski, 1992), including separation difficulties, excessive fear, agitation, aggression, and suicidal behavior.…”
Section: Psycho Log Ica 1 Impactmentioning
confidence: 96%
“…The loss of paid employment, or even a reduction in vocational status to a lower level of remuneration or to part-time employment, can be financially devastating, particularly for young people with families. Indeed, more than 30% of a sample of people injured in MVAs indicated that they had experienced a major reduction in income as a result of their injury (Landsman et al, 1990). In terms of the broad economy, the finan-58 E. Kendall and N .…”
Section: Vocational Functioningmentioning
confidence: 99%
See 1 more Smart Citation